PEMERIKSAAN LABORATORIUM UNTUK DIAGNOSIS LEPTOSPIROSIS - Debie Anggraini (Stikes Syedza Saintika, 2021)
Leptospirosis is a zoonotic disease with the main source of transmission in humans from rats, dogs, cattle, and pigs. Leptospira icterohemorrhagiae is a Leptospira serovar that infects rats. Leptospires live in the kidneys/urinary tract of these animals without causing disease and continuously flowing in the urine. Leptospira examination was carried out using a phase contrast microscope or dark field. Leptopira requires special media and conditions to grow and its culture takes a long time. Serological examination is the main basis in the diagnosis of leptospirosis. The reference method of serological examination for leptospirosis is the microscopic agglutination test (MAT).